PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATA PELAJARAN PERAWATAN WAJAH BERJERAWAT DENGAN MENGGUNAKAN PENDEKATAN BERPIKIR KRITIS DI SMK NEGERI 1 SOOKO - Baharia Putri Kusuma; Biyan Yesi Wilujeng; Sri Usodoningtyas; Mutimmatul Faidah (Program Studi Pendidikan Tata Rias, 2024)
One of the ways in which teaching objectives have been achieved can be seen from the learning achievements achieved by students. Project Based Learning is an innovative, project-based, student-centered learning model. Critical thinking. Acne facial treatment is an action that is deliberately carried out for skin that has facial skin problems, including acne, oily facial skin, hyperpigmentation, and blackheads. This research aims to 1) the implementation of the learning model, 2) student learning outcomes, 3) students' ability to think critically, 4) student responses, with reference to data collection instruments 1) syntax implementation observation sheet, 2) student performance sheet, 3) critical thinking assessment sheet, 4) student response questionnaire sheet. The research used by researchers is a pre-experimental design research method using a one-shot case study research model using a quantitative approach. The subjects of this research were 29 grade 12 skin and hair beauty students who had received facial care material. The research results showed that 1) the implementation of learning syntax obtained an average of all aspects, namely 90% in the